2011
DOI: 10.1371/journal.pone.0020372
|View full text |Cite
|
Sign up to set email alerts
|

Expression of OATP Family Members in Hormone-Related Cancers: Potential Markers of Progression

Abstract: The organic anion transporting polypeptide (OATP) family of transporters has been implicated in prostate cancer disease progression probably by transporting hormones or drugs. In this study, we aimed to elucidate the expression, frequency, and relevance of OATPs as a biomarker in hormone-dependent cancers. We completed a study examining SLCO1B3, SLCO1B1 and SLCO2B1 mRNA expression in 381 primary, independent patient samples representing 21 cancers and normal tissues. From a separate cohort, protein expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 20 publications
6
107
1
Order By: Relevance
“…In fact, our primary target, SLCO1B3 is aberrantly expressed in a panel of cSCC from both UV induced and RDEB induced cSCC cell lines and tissue (Fig. 1), again in agreement with previous studies identifying SLCO1B3 expression in cancer (Maeda et al, 2010;Pressler et al, 2011;Svoboda et al, 2011). However, by pursuing the molecule responsible for RDEB we show that type VII collagen regulates the expression of SLCO1B3 in both RDEB cSCC and Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, our primary target, SLCO1B3 is aberrantly expressed in a panel of cSCC from both UV induced and RDEB induced cSCC cell lines and tissue (Fig. 1), again in agreement with previous studies identifying SLCO1B3 expression in cancer (Maeda et al, 2010;Pressler et al, 2011;Svoboda et al, 2011). However, by pursuing the molecule responsible for RDEB we show that type VII collagen regulates the expression of SLCO1B3 in both RDEB cSCC and Fig.…”
Section: Discussionsupporting
confidence: 90%
“…OATP1B3 is normally expressed in the liver and is involved in the transport of bile salts, glutathione and other organic anions (Smith et al, 2005a;Hagenbuch and Gui, 2008). In agreement with our data, OATP1B3/SLCO1B3 is frequently upregulated in solid tumours including breast and colon Maeda et al, 2010;Pressler et al, 2011) and it has been suggested that OATP1B3 has therapeutic potential owing to its ability to transport a broad range of drugs, including methotrexate, paclitaxel, docetaxel, bromsulphalein (BSP) and pitavastatin (Smith et al, 2005b;Hagenbuch and Gui, 2008). OATP1B3 expression has been reported to associate with clinical outcome in a number of studies (Hamada et al, 2008;Lockhart et al, 2008) yet little data exist on the mechanism of expression or functional consequence.…”
Section: Introductionsupporting
confidence: 91%
“…Certain (60) ↑ in prostate cancer cells (6) qRT-PCR Kidney (64) ↑ in bone cancer (65) RT-PCR OATP1B1 Liver (2,66) ↓ in liver cancer (37)(38)(39)67,68) RT-PCR, IF, IB ↑ in colon polyps and colon cancer (63) RT-PCR ↑ in ovarian cancer (69) RT-PCR OATP1B3 Liver (3,70) ↓ in liver cancer (41) qRT-PCR, IB ↑ in colon cancer (4,71,72) RT-PCR, qRT-PCR, IB, IHC ↑ in pancreatic cancer (71)(72)(73) RT-PCR, qRT-PCR, IB, IHC ↑ in lung cancer (38) RT-PCR, qRT-PCR, IF ↑ in prostate cancer (16,17,68,74) qRT-PCR, IF ↑ in breast cancer (75) qRT-PCR, IHC ↑ in testicular cancer (68) qRT-PCR, IF ↑ in ovarian cancer (69) RT-PCR OATP1C1 Brain (76) ↑ in bone cancers (65) RT-PCR Testes (76) Ciliary body (77) OATP2A1 Ubiquitous (78) ↑ in breast cancer (79) qRT-PCR ↑ in liver cancer (80) qRT-PCR, IF ↑ in bone metastases from kidney cancer (65) qRT-PCR, IB ↓ in cancers of bowel, stomach, ovary, lung, and kidney (81) RT-PCR OATP2B1 Blood-brain barrier (82) ↑ in bone cancer (65) RT-PCR Heart (83) ↑ in breast cancers (79,84) qRT-PCR, IF, IB Enterocytes (85) ↓ in liver and pancreatic cancers (68) qRT-PCR Liver (86) Placenta (87) OATP3A1 Ubiquitous (88) ↑ in bone cysts …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Pressler et al showed that OATP2B1 mRNA expression was lower in liver and pancreatic cancers compared to that in nonmalignant tissues (68). However, these findings have not been validated at the protein level.…”
Section: Oatp2b1 (Gene Symbol Slco2b1)mentioning
confidence: 99%
“…Testosterone is a substrate for OATP1B3, and OATP1B3 expression has been shown to be associated with Gleason score. 8 While AR-V7 may be useful for predicting treatment response with enzalutamide and abiraterone, other potential biomarkers, like CYP1B1 Ã 3 and OATP1B3, may be better predictors of taxane efficacy in CRPC patients. Antonarakis et al mentions in both their 2014 study and their most recent study a phenomenon of AR-V7 status conversion.…”
mentioning
confidence: 99%